2017
DOI: 10.5937/savteh1701005c
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-galactosidase from Lactobacillus acidophilus: Stability and kinetic study

Abstract: β-Galactosidase is the industrially important enzyme that catalyzes both, lactose hydrolysis and synthesis of different bioactive galactosides. In this study, optimal conditions (fermentation temperature, inoculum concentration and lactose concentration) for accomplishing high yields of β-galactosidase activity from Lactobacillus acidophilus ATCC 4356, bacteria regarded as safe for human consumption, were investigated. Using the response surface methodology (RSM), it was concluded that the highest activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several models were developed using the various mechanistic sequences of steps shown in Table , with between five and eight kinetic parameters. In this paper, models involving product inhibition will not be considered, because in our previous studies, , the inhibitory effect was not observed.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Several models were developed using the various mechanistic sequences of steps shown in Table , with between five and eight kinetic parameters. In this paper, models involving product inhibition will not be considered, because in our previous studies, , the inhibitory effect was not observed.…”
Section: Model and Methodologymentioning
confidence: 99%
“…Based on Mahoney (2004), lactose could act as an inducer in βgalactosidase production. A study by Carevic et al (2017) mentioned that β-galactosidase enzyme activity in Lactobacillus acidophilus increased with the addition of 1.48% lactose. Carevic et al (2015) stated that enzyme activity of β-galactosidase increased gradually when the fermentation started and would achieve maximum activity on stationary phase after two days, but then experienced a decrease in activity afterward.…”
Section: Optimum Growth Condition Of Lactobacillus Brevis Lipi13-2-lamentioning
confidence: 99%
“…Carevic et al (2015) also mentioned that the optimum time to achieve maximum βgalactosidase enzyme activity was 48 hours. Based on the research conducted by Carevic et al (2017), there was effect between inoculum size and β-galactosidase enzyme activity. β-galactosidase enzyme activity of Lactobacillus acidophilus increased by the addition of 2.8% inoculum size.…”
Section: Optimum Growth Condition Of Lactobacillus Brevis Lipi13-2-lamentioning
confidence: 99%